Analisa Tahapan Pengajaran Bilingual Bagi Siswa Sekolah Dasar di Indonesia - Utami, Arinta Widya Kasi; Nirwasita, Paramesti; Ramhawati, Ely Eka; Permatasari, Rikha; Qorneila, Yutika; Budiarso, Yunita Sari; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to describe the ideal stages in bilingual teaching for elementary school students in Indonesia. This study is a qualitative study with a case study method through a literature review of scientific articles, journals, and other academic publications. The subjects of this study were elementary school students in Indonesia. The results of the analysis show that the implementation of bilingual teaching in elementary schools consists of three main stages, namely 1) the introduction stage (early exposure), which focuses on the introduction of basic vocabulary in two languages; 2) the development stage (developing bilingual proficiency), which encourages students to apply the second language in everyday life through the Content and Language Integrated Learning (CLIL) and English Conversation methods, and 3) the consolidation stage (fluency & academic integration), where students are expected to be fluent in using the second language and integrated with academic subjects. The success of bilingual teaching is influenced by school management factors, teacher readiness, and support from parents and the community. This study is expected to be a basis for educators, curriculum designers, and policy makers in developing effective bilingual learning.